2015
DOI: 10.1590/1678-457x.6745
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and functionality of millet supplemented pasta

Abstract: Millets are having superior nutritional qualities and health benefits; hence they can be used for supplementation of pasta. Pasta was prepared using composite flour (CF) of durum wheat semolina (96%) and carrot pomace (4%) supplemented with finger millet flour (FMF,, pearl millet flour (PMF, 0-30g) and carboxy methyl cellulose (CMC, 2-4g). Second order polynomial described the effect of FMF, PMF and CMC on lightness, firmness, gruel loss and overall acceptability of extruded pasta products. Results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
4
22
0
1
Order By: Relevance
“…Similar result was also obtained in noodle prepared from millet incorporated flour by Vijayakumar et al, (2010) whereas contrast result was reported by Gull et al, (2015) with regards to millet supplemented pasta.…”
Section: Cooking Qualitysupporting
confidence: 85%
See 1 more Smart Citation
“…Similar result was also obtained in noodle prepared from millet incorporated flour by Vijayakumar et al, (2010) whereas contrast result was reported by Gull et al, (2015) with regards to millet supplemented pasta.…”
Section: Cooking Qualitysupporting
confidence: 85%
“…The increase in supplementation of foxtail millet decreases the solid in cooking water that proved the percent loss of solids was minimum for foxtail millet. Similar result was also obtained in noodle prepared from millet incorporated flour by Vijayakumar et al, (2010) whereas contrast result was reported by Gull et al, (2015) with regards to millet supplemented pasta.…”
Section: Cooking Qualitysupporting
confidence: 85%
“…In general, millets are limited in lysine and tryptophan content and vary with cultivar. However, most cereals contain the essential amino acids as well as vitamins and minerals (Devi, Vijayabharathi, Sathyabama, Malleshi, & Priyadarisini, 2011;FAO, 2009;Gull, Kmalesh, & Kumar, 2015).…”
mentioning
confidence: 99%
“…So, gluten-free grains as base ingredient are the only alternate to get rid from these inconveniences. Frequent consumption pattern of these consumables draw researcher's attention to exploit different grains, additives, industrial byproducts, and process optimization tools through numerical modeling to have range of healthy and nutritious food choice among consumers with longterm storage capability (Gull, Prasad, & Kumar, 2015). High sugar and fat utilization pose storage stability defects due to the hygroscopic nature of sugar and rancidity development on account of fat, respectively.…”
mentioning
confidence: 99%